Free surface due to a flow driven by a rotating disk inside a vertical cylindrical tank: Axisymmetric configuration - Kahouadji,L; Witkowski,LM (Physics of Fluids, 2014)
The flow driven by a rotating disk at the bottom of an open fixed cylindrical cavity is studied numerically and experimentally. The steady axisymmetric Navier-Stokes equations projected onto a curvilinear coordinate system are solved by a Newton-Raphson algorithm. The free surface shape is computed by an iterative process in order to satisfy a zero normal stress balance at the interface. In previous studies, regarding the free surface deflection, there is a significant disagreement between a first-order approximation [M. Piva and E. Meiburg, “Steady axisymmetric flow in an open cylindrical container with a partially rotating bottom wall,” Phys. Fluids17, 063603 (2005)] and a full numerical simulation [R. Bouffanais and D. Lo Jacono, “Unsteady transitional swirling flow in the presence of a moving free surface,” Phys. Fluids21, 064107 (2009)]. For a small deflection, the first-order approximation matches with our numerical simulation and for a large deflection a good agreement is found with experimental measurements.